HUBUNGAN POLA ASUH ORANGTUA DENGAN KEMANDIRIAN KEBERSIHAN PERORANGAN PADA ANAK PRA SEKOLAH DI TAMAN KANAK-KANAK KARTIKA MANADO - Matfikih, Nurfiana; Warouw, Sarah M.; Rottie, Julia (e-NERS)
Abstract: Independence of self is one of the most important aspects that should be possessed by each individual and the child, because in addition to affect performance, it also serves to help achieve the goal of life, achievements, success and earn rewards. Without the support of an independent nature, the individual and the child will be difficult to reach something in the maximum, and it will also be difficult to achieve succes. TheÂ  support of parents and the right of parenting, in accordance with conditions expected to establish children in pre-school indepedence in the exercise of an daily personal hygiene. This research to know the relationship of parenting parents with personal hygiene independence to children in pre-school at Kindergarten of Kartika Manado. The design of this study using the cross sectional approach. The method of sampling in this study is a total sampling way that some 50 parents/guardians of students. This study used a questionnaire instrument and analys Chi-Square statistical test at a significance level of 95 %: (Î± 0,05). The result showed there were 19 samples that had authotitarian parents, 12 samples didnâ€™t have the independence in maintaining personal hygiene and 7 samples are independent. There are 31 samples that have parents democratic, 7 samples donâ€™t have the independence in maintaining personal hygiene and 24 samples are independent. Result of Chi-Square test (X2) at 95 % confidence level (Î± 0,05), showed an association with parenting parents with personal hygiene independence to children in pre-school at Kindergarten of Kartika Manado, where the value of Ï=0,004, smaller than Î±=0,05. Democratic parenting was able to indepedence to children to maintain personal hygiene, itâ€™s expected that managers at Kindergarten of Kartika Manado to promote democratic parenting to parents, so that parents can implement it in the family life. Keywords: The Parenting Parents, personal hygiene independence to children in pre-school. Â  Â  Abstrak: Kemandirian merupakan salah satu aspek terpenting yang harus dimiliki setiap individu dan anak, karena selain dapat mempengaruhi kinerja, juga berfungsi untuk membantu mencapai tujuan hidup, prestasi, kesuksesan serta memperoleh penghargaan. Tanpa didukung oleh sifat mandiri, maka individu maupun anak akan sulit untuk mencapai sesuatu secara maksimal, dan akan sulit pula untuk meraih kesuksesan. Dukungan orangtua serta pola asuh yang tepat, sesuai dengan keadaan anak diharapkan mampu membentuk kemandirian anak pra sekolah dalam pelaksanaan kebersihan perorangan sehari-hari. Penelitian ini bertujuan untuk mengetahui hubungan pola asuh orangtua dengan kemandirian kebersihan perorangan pada anak pra sekolah di Taman Kanak-Kanak Kartika Manado. Rancangan penelitian ini menggunakan pendekatan cross sectional. Cara pengambilan sampel dalam penelitian ini adalah dengan cara total sampling yaitu sejumlah 50 orangtua/wali siswa. Penelitian ini menggunakan instrumen kuesioner dan dianalisa menggunkan uji statistic Chi-Square pada tingkat kemaknaan 95 %: (Î± 0,05). Hasil penelitian menunjukkan dari 19 sampel yang memiliki orang tua otoriter, 12 sampel tidak memiliki kemandirian dalam menjaga kebersihan perorangan dan 7 sampel memiliki kemandirian. Dari 31 sampel yang memiliki orang tua demokratis, 7 sampel tidak memiliki kemandirian dalam menjaga kebersihan perorangan dan 24 sampel memiliki kemandirian. Hasil uji Chi Square (X2) pada tingkatÂ  kepercayaan 95% (Î± 0,05), menunjukkan ada hubungan hubungan pola asuh orangtua dengan kemandirian kebersihan perorangan pada anak pra sekolah di Taman Kanak-Kanak Kartika Manado, dimana nilai Ï= 0,004, lebih kecil dari Î±=0,05. Pola asuh demokratis ternyata mampu memandirikan anak pra sekolah untuk menjaga kebersihan perorangan, diharapkan agar pengelola Taman Kanak-Kanak Kartika Manado mensosialisasikan pola asuh demokratis kepada orang tua, agar orang tua dapat mengimplementasikannya di dalam kehidupan berkeluarga. Kata Kunci: Pola Asuh Orangtua, Kemandirian Kebersihan Perorangan Anak Pra Sekolah.